The effect of basketball matches on salivary markers: a systematic review - Kamarauskas, Paulius; Conte, Daniele (Biology of Sport, 2022)
The aim of this paper was to synthesize the findings on salivary marker responses to the different basketball match typologies. An electronic database search of articles published until October 2020 was performed in PubMed, SPORTDiscus, Scopus and Web of Science. Studies were then screened using pre-defined selection criteria and a subsequent assessment of methodological quality was conducted. Articles matching the selection criteria and methodological quality were included in the systematic review. The electronic database search produced 696 articles. After removing 505 duplicates, 191 articles were included for screening. Screening led to 10 articles that met the inclusion criteria. The main findings revealed that playing a basketball match induced a highly stressful condition reflected by increased post-match cortisol levels regardless of season phase (i.e. regular vs. semi-final vs. final matches), match outcome (i.e. winning vs. losing matches) and location (i.e. home vs. away). Different results were found for testosterone, which showed inconsistent outcomes when measured before and after matches. However, an effect of match location on testosterone levels was observed, with higher concentrations before home matches compared to away matches. Finally, playing basketball matches led to an increase in levels of alpha-amylase, a decrease in interleukin-21 and no changes in immunoglobulin A, total protein and brain-derived-neurotrophic factor. The current results provide a detailed description of salivary markers changes in response to different basketball matches, which can help practitioners to have a better understanding of the basketball performance profile.